(untitled) (Revista Ibero-Americana de Ciência da Informação, 2022)
It presents a proposal for a relationship between Integrated Archival Science and Research Data Management based on the development of archival functions recommended by Canadian authors Jean-Yves Rousseau and Carol Couture. It approaches Research Data Management as a multidisciplinary activity and develops the role of Archival Science in Research Data Management. It demonstrates the potential of integrating the two disciplines.